1996
DOI: 10.1016/s1382-6689(96)00070-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of the mouse brain Mn-SOD by methylmercury

Abstract: Changes in mRNA levels, protein contents and enzyme activities for brain Cu,Zn- and Mn-SOD by methylmercury chloride (MMC) administration, were examined, over a period of 12 days in ICR male mice. After subcutaneous administration of MMC (10 mg/kg) to mice, brain mercury content reached a maximum at 2 days and remained at that level for at least 5 days. MMC exposure resulted in a time-dependent decrease in the Mn-SOD activity: the enzyme activity at 5 days after exposure to MMC was about 60% of control level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
1
33
0
2
Order By: Relevance
“…The authors didn't determine which isozyme was involved in the enzyme loss, but eukaryotic cells contain two types of SODs, copper and zinc SOD (Cu,Zn-SOD) and manganese SOD (Mn-SOD). We later found that Mn-SOD is susceptible to being modifi ed by MeHg and that Cu,Zn-SOD is not (Shinyashiki et al, 1996). Exposing mice to MeHg at a dose of 10 mg/kg only once resulted in a time-dependent decrease in Mn-SOD activity but had little effect on Cu,Zn-SOD activity in the brain.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors didn't determine which isozyme was involved in the enzyme loss, but eukaryotic cells contain two types of SODs, copper and zinc SOD (Cu,Zn-SOD) and manganese SOD (Mn-SOD). We later found that Mn-SOD is susceptible to being modifi ed by MeHg and that Cu,Zn-SOD is not (Shinyashiki et al, 1996). Exposing mice to MeHg at a dose of 10 mg/kg only once resulted in a time-dependent decrease in Mn-SOD activity but had little effect on Cu,Zn-SOD activity in the brain.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 94%
“…They found that the sensitivity of HeLa cells to MeHg was decreased by the overexpression of Mn-SOD, suggesting that the formation of superoxide anions in the mitochondria might be involved in the mechanism(s) involved in the cytotoxicity of MeHg. We have attempted to examine the mechanism involved in the relationship between Mn-SOD and MeHg (Kumagai et al, 1997;Shinyashiki et al, 1996). Levels of mRNA and protein synthesis for Mn-SOD were unaffected by MeHg administration.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 99%
“…Methylmercury (MeHg) is an electrophile that modifies cellular proteins, resulting in enzyme dysfunction and cell damage (Shinyashiki et al, 1996). We previously reported that MeHg activates NF-E2-related factor 2 (Nrf2), a transcription factor involved in cellular protection against MeHg toxicity in human neuroblastoma SH-SY5Y cells (Toyama et al, 2007(Toyama et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Mn-SOD activities were determined by reduction of acetylated cytochrome c in the presence of potassium cyanide, as described previously (Shinyashiki et al 1996). The reaction mixture (1.5 ml) consisted of 0.05 mM xanthine, 44 nM xanthine oxidase, 25 lM acetylated cytochrome c, the enzyme preparation and 50 mM potassium phosphate buffer (pH 7.8)/0.01 mM EDTA.…”
Section: Mn-sod Activity In Vivo and In Vitromentioning
confidence: 99%
“…We have previously demonstrated that in mice subcutaneous injection of methylmercury chloride, at a dose of 10 mg/ kg, which affects the central nervous system because of its predominant accumulation there (Clarkson 1972), results in a reduction of the brain manganese SOD (Mn-SOD) activity (Shinyashiki et al 1996). The importance of Mn-SOD for protection against methylmercury toxicity was subsequently reported by Naganuma et al (1998).…”
Section: Introductionmentioning
confidence: 98%